Analysis of flood events in sub-basin Carneirinhos, João Monlevade, Minas Gerais (Research, Society and Development, 2020)
Since the 1940s, the number of people living in Brazilian cities doubled, however, the process of cities growth has occurred in a disordered manner, resulting in several socio-environmental problems, mainly during the rainy season, when the events of floods and landslides are more frequent. João Monlevade is a municipality in Minas Gerais that has a history of disasters. Thus, this study aims to analyze the flooding events recorded in the Carneirinhos sub-basin, located in João Monlevade, Minas Gerais state, their impacts, as well as the meteorological systems acting in the occurrence period. Firstly, the study area was delimited and characterized, data collection related to the historical series of flood events that occurred in the hydrographic sub-basin of the Carneirinhos stream, during the period from 1969 to 2020, was carried out. Secondly, the meteorological systems acting on the event data were identified. From the results obtained, it is possible to verify that Carneirinhos stream recorded 14 flood events according to the management organizations of the municipality. These events are mainly associated with the South Atlantic Convergence Zone or with Humidity Convergence Zones. Some possible factors that may justify an occurrence of these events are changes in hydrological patterns due to climate change, the stream’s canalization, possible flaws in the design of the basin drainage system design, and / or a combination of all these factors. Finally, it is recommended that studies be carried out on the current drainage system in the municipality, addressing the dimensioning of the existent galleries to face future changes, since some studies point to an increase in the frequency of flood events.